On Q-Euclidean L-fuzzy Ideals of Rings - Balkanay, Erol; KOÇ, AYTEN (TÜBİTAK, 2004)
In this paper we define a θ-Euclidean level subset and a θ-Euclidean level ideal. We also give some properties of a θ-Euclidean level subset.
Keywords: Ideal; fuzzy ideal; level subset; Q-Euclidean level ideal; Q-Euclidean L-fuzzy ideal